Sengketa Ekonomi Syariah Diselesaikan Sesuai Dengan Persyaratan Yang Diatur Mahkamah Agung (International Forum of Researchers and Lecturers, 2023)
The large number of people who use sharia contracts has a strong correlation with the number of sharia economic conflicts. Either party may breach the contract or engage in illegal acts giving rise to law. If a lawsuit occurs, the aggrieved party can file a lawsuit against the lawsuit, but the judge turns out that during the examination of the case, it determines that the contract in question is not in accordance with sharia law, even though neither party owns it. filed a lawsuit to be terminated. To examine sharia economic dispute cases, judges are required to follow certain provisions from the Supreme Court. In this study, the authors also used a conceptual approach to examine. Islamic legal concepts related to improper contracts. govern Islam. The authors of this study draw the conclusion that there are still many legal discussions governing sharia economics; existing laws only regulate in general and globally, and sometimes even conflict with each other. Due to loopholes in the law, the Supreme Court established guidelines for reviewing sharia economic cases. The guidelines contain several provisions that are inconsistent or even contradict one another, so that ijtihad is required from the judge's side to uphold the principle of divinity. so that the choice is only based on the rules stipulated by Islamic law. then the Supreme Court sets guidelines for reviewing sharia economic cases. The guidelines contain several provisions that are inconsistent or even contradict one another, so that ijtihad is required from the judge's side to uphold the principle of divinity. so that the choice is only based on the rules stipulated by Islamic law.. then the Supreme Court sets guidelines for reviewing sharia economic cases. The guidelines contain several provisions that are inconsistent or even contradict one another, so that ijtihad is required from the judge's side to uphold the principle of divinity. so that the choice is only based on the rules stipulated by Islamic law.